Interactive Media with Android Based Sign Language as an Effort to Improve Dental Health Maintenance Behaviour and Decrease Debris Index in Deaf Children - Apriyanti, Lidya Dwi; Fatmasari, Diyah; Supriyana, Supriyana; Wiyatini, Tri; Djamil, Masrifan (Jurnal Kesehatan Gigi, 2025)
Deaf children in the intervention group had 100% caries and an average debris index of 80%, indicating poor dental and oral hygiene. To address this issue, interactive media with Android-based sign language and game methods was used for engaging and enjoyable learning. This research aims is used to produce interactive media with android-based sign language as an effort to improve dental health maintenance behavior and decrease debris index in deaf children. This research method is Mixed Method and Research and Development (R&D) research design. There are five stages of research, namely: information collection, model design, expert validation and revision, model testing with quasi-experimental methods with pre-test design – post-test control group design. The results of interactive media with Android-based sign language according to expert validation average 95% and p value = 0.007 (very feasible). The results of the paired data effectiveness test in the intervention group with a knowledge value of p = 0.008 with a delta value of 2.666, attitude value p = 0.005 with a delta value of 3.916, skill value p = 0.004 with a delta value of 6.250, debris index score p = 0.001 with a delta value of 1.350, compared to the control group. So that this interactive media with android-based sign language is feasible and its application is effective as an effort to improve dental health maintenance behavior and reduce debris index in deaf children.